The technical interview guide to investment banking - Pignataro, Paul (Online access with DDA: Askews (Economics), 2017)
Win the recruiting race with the ultimate analyst's guide to the interview The Complete, Technical Interview Guide to Investment Banking is the aspiring investment banker's guide to acing the interview and beginning your journey to the top. By merging a 'study guide' to the field with a forecast of the interview, this book helps you prepare for both content and structure; you'll brush up on important topics while getting a preview of the questions your interviewers are likely to ask. Covering financial statements, valuation, mergers and acquisitions, and leveraged buyouts, the discussion provides the answers to common technical questions while refreshing your understanding of the core technical analyses behind core models and analyses. Each chapter includes a list of the questions you will almost certainly be asked-along with the answers that interviewers want to hear-from the basic Q & A to the advanced technical analyses and case studies. This guide will reinforce your knowledge and give you the confidence to handle anything they can throw at you. You will receive an expert synopsis of the major points you need to know, to ensure your understanding and ability to handle the multitude of questions in each area.-Double-check your conceptual grasp of core finance topics -Plan your responses to common technical and analysis questions -Understand how to analyze and solve technical analyses and cases -Gain insight into what interviewers want to hear from potential hires -Become the candidate they can't turn away You've positioned yourself as a competitive candidate, and the right job right now can chart your entire career's trajectory. Now you just have to win the recruiting race. The Complete, Technical Interview Guide to Investment Banking is the ultimate preparation guide to getting the job you want.